2014
DOI: 10.2147/dddt.s63753
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial, antimicrobial, and biocompatibility properties of para-aminosalicylic acid with zinc layered hydroxide and Zn/Al layered double hydroxide nanocomposites

Abstract: The treatment of tuberculosis by chemotherapy is complicated due to multiple drug prescriptions, long treatment duration, and adverse side effects. We report here for the first time an in vitro therapeutic effect of nanocomposites based on para-aminosalicylic acid with zinc layered hydroxide (PAS-ZLH) and zinc-aluminum layered double hydroxides (PAS-Zn/Al LDH), against mycobacteria, Gram-positive bacteria, and Gram-negative bacteria. The nanocomposites demonstrated good antimycobacterial activity and were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, in basic conditions, formation precipitation of metal ions as their respective hydroxide can influence the adsorption results, therefore we have selected the maximum adsorption under acidic environment e.g. <pH 7 2426 . Lead ions showed the highest adsorption of about 95.20% at pH 4 and the remaining three metal ions Cr 6+ , Cd 2+ and Zn 2+ , pH 6 was found to be the optimum with maximum adsorption of 90.20%, 75.50% and 67.30%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, in basic conditions, formation precipitation of metal ions as their respective hydroxide can influence the adsorption results, therefore we have selected the maximum adsorption under acidic environment e.g. <pH 7 2426 . Lead ions showed the highest adsorption of about 95.20% at pH 4 and the remaining three metal ions Cr 6+ , Cd 2+ and Zn 2+ , pH 6 was found to be the optimum with maximum adsorption of 90.20%, 75.50% and 67.30%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the antibacterial property of HA is less obvious, and it could affect the remineralization process since the acidic environment causing the demineralization is produced by specific types of bacteria. It has been reported that zinc inhibits dental plaque formation in vivo due to its antibacterial effect [6]. Considering plaque removal can prevent enamel demineralization, we assume that hydroxyapatite with zinc ions would weaken the demineralization of enamel.…”
Section: Introductionmentioning
confidence: 98%
“…Hybridizing oleanolic acid with 4-aminosalicylic acid resulted in compound 4 with enhanced antibacterial activity against certain strains of bacteria. 4-Aminosalicylic acid has been reported to inhibit E. coli growth (Saifullah et al 2014).…”
Section: Resultsmentioning
confidence: 99%